Methodical Recommendations on the Formation of an Optimized Network of Vocational Training (Vocational Technical Training) Institutions in Keeping with the Needs of Regional Labor Markets - Liesnikova М. V. (Statistics of Ukraine, 2020)
Optimization of the network of vocational training (vocational technical training) institutions (VT(VTT)Is) calls for creating new multidisciplinary and multilevel institutions and reorganizing (merging or transforming) the existing ones in order to provide vocational training services and build a model of the multipurpose center of professional excellence. This optimization is admitted by the overwhelming majority of scientists and experts as a necessary process allowing for optimization of resources, with streamlining them on quality enhancement of the professional training of the workforce. The core mechanisms for building up an optimized network consist of VT(VTT)Is integration and enlargement processes. The article contains an analysis of the processes taking place within the VT(VTT)Is network, with formulating methodical recommendations on its optimization. A stable downward tendency in the number of VT(VTT)Is and the respective decline in the number of trained persons are shown. The number of VT(VTT)Is decreased by 13 (or 1.8%) in 2019 compared with the previous year, and by 33 (or 4.4%) compared with 2017. The overall downward tendency in the number of VT(VTT)Is is accompanied by the following processes: reorganization and restructuring, dominated by incorporations in a larger institution, mergers of two or three institutions with establishing new ones on their basis, most commonly referred to as Regional Center of Professional-Technical Education; liquidations, changes of the status or title; withdrawals from or incorporations in the network depending on the existence or absence of a regional order for training of workers. The author argues that recommendations on forming an optimized VT(VTT)Is network in keeping with the needs of regional labor markets should be based on the computed integral index of the institution’s operation. According to the proposed method, the integral index of the institution’s operation is a synthetic index derived from factor analysis on the basis of a comprehensive set of statistical data and expert assessments on the institution’s operation. Computations of the integral index of the institution’s operation at city, region or country level can provide a rank for each institution, which will enable to substantiate the necessary measures for it as part of the overall network optimization with consideration to the needs of the regional labor markets.